2018
DOI: 10.3390/ijerph15102216
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported vs. Measured Height, Weight, and BMI in Young Adults

Abstract: Self-reported height and weight, if accurate, provide a simple and economical method to track changes in body weight over time. Literature suggests adults tend to under-report their own weight and that the gap between self-reported weight and actual weight increases with obesity. This study investigates the extent of discrepancy in self-reported height, weight, and subsequent Body Mass Index (BMI) versus actual measurements in young adults. Physically measured and self-reported height and weight were taken fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 27 publications
(30 reference statements)
4
108
1
1
Order By: Relevance
“…These included: sex, marital status, income, race, university major, tuition payment plan, academic year, general health, age and self-reported anthropometrics (weight and height). Self-reported measurement has been found to be both valid and reliable when compared to measurements taken directly by researchers [29][30][31]. Body mass index (BMI) was calculated using reported weight and height, dividing the weight in kilograms on the squared height in meters.…”
Section: Variablesmentioning
confidence: 99%
“…These included: sex, marital status, income, race, university major, tuition payment plan, academic year, general health, age and self-reported anthropometrics (weight and height). Self-reported measurement has been found to be both valid and reliable when compared to measurements taken directly by researchers [29][30][31]. Body mass index (BMI) was calculated using reported weight and height, dividing the weight in kilograms on the squared height in meters.…”
Section: Variablesmentioning
confidence: 99%
“…In addition, studies that were conducted in larger, more diverse samples were done in the early 2000s, warranting updated studies to explore whether trends of reporting measurements have changed (23,24) . Further research is needed to compare the accuracy of self-reported data with objectively measured height, weight and BMI in large adolescent populations (25) . Thus, the aims of the present study were to examine the accuracy of self-reported height, weight and resultant BMI values, and to describe gender differences in the level of agreement between objectively measured and self-reported values in a sample of high school students in different U.S. states.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is that height and weight at T6 were self‐reported, while trained research assistants measured participants' weight and height at T1 to T5. Previous studies among young adults suggest that, despite some evidence of under‐ and overestimation, self‐reported height and weight are accurate enough to generate a valid BMI in the majority of cases (Olfert et al, ; Quick et al, ). In addition, it should be noted that we only included participants with complete data in each analysis.…”
Section: Discussionmentioning
confidence: 99%